PENGEMBANGAN PELABUHAN BELAWAN DAN PENGARUHNYA TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DELI, 1920-1942 - Novita Mandasari Hutagaol (Department of History, Faculty of Humanities, Diponegoro University, 2016)
Belawan port development in the end of the IX century and the early twentieth century had made only one port of Belawan port of export-import of the largest in East Sumatra as well as being one of the host ports in the East Indies. The development of plantations in the interior of East Sumatra has prompted the colonial government to develop the port of Belawan both in physical context, and as well as management tools. The port establishment such as dredging sludge, docking construction, storage warehouses, office buildings, roads, and railway lines. It was provided by some facilities such as electricity supply and clean water. In the field of port management of Belawan managed to become modern port company (bedrij haven). The development of Belawan port resulted on the increasing of import-export revenue in Deli and the surrounding regions. The influence of its development was about changes on citiy’s morphology, population, trade, labor, and social infrastructure.